ANALISIS ISI UNSUR KEBUDAYAAN LOKAL DAN NASIONAL DALAM BUKU AJAR BIPA SAHABATKU INDONESIA B1 - Suryadi, Sopinatul; Rizka Aulia Insani; Anisa Ulfiani; Sindi Karina Sari; Santika; Nuril Indana Ramadani; Baiq Rismariny Nursaly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian for Foreign Speakers (BIPA) learning focuses not only on linguistic proficiency but also on developing pragmatic competence and intercultural awareness. This study aims to analyze the distribution, manifestations, and integration of local and national cultural elements contained in the "Catatan Budaya" (Cultural Notes) sub-sections of the B1 textbook "Sahabatku Indonesia," published by the Language Development and Fostering Agency. Grounded in E.B. Tylor's (1871) conceptualization of culture as a "complex whole" encompassing material and non-material dimensions, this qualitative descriptive study examined 12 learning units using content analysis. Data were collected through documentation study and text codification. The results indicate that the textbook systematically and proportionally presents local and national cultural elements. Local culture is manifested through material aspects such as traditional crafts ("Kain Songket") and performance props, as well as non-material aspects such as regional dances ("Saman," "Jaipong," "Tari Lilin"). National culture appears predominantly through non-material dimensions, including politeness norms, traditional medicine ("kerokan"), market interactions, and Independence Day traditions ("Panjat Pinang"). The integration of these cultural elements is closely aligned with grammatical structures (such as passive voice as a hedging strategy) and offers pedagogical implications for preventing pragmatic failure while fostering intercultural awareness among intermediate BIPA learners.